Regulatory impact of possible radon prevention measures in new build homes in Ireland - Sean Lyons; Katie Duffy; Anne Nolan (The Economic and Social Research Institute (ESRI), 2023)
The purpose of this report is to undertake an ex-ante evaluation of the cost effectiveness of alternative radon prevention measures for new build properties in Ireland. Radon is a naturally occurring gas that primarily enters a building by seeping through the ground floor. Radon is the predominant source of radiation in Ireland, the second most prominent cause of lung cancer after smoking, and the number one cause of lung cancer amongst people who have never smoked. One of the most common prevention methods for new buildings is the installation of an airtight radon-proof membrane across the foundation.
Keywords: 330